2009 IEEE International Conference on 3D System Integration 2009
DOI: 10.1109/3dic.2009.5306578
|View full text |Cite
|
Sign up to set email alerts
|

3-D thin chip integration technology - from technology development to application

Abstract: 3-D technologies open a wide range of chip integration possibilities for microelectronic systems.Most of these technologies are using Through-Silicon Vias (TSV). One disadvantage of this technology is the high investment for new equipment and processing cost for Si etching and metallization. The thin chip integration technology (TCI) presented in this paper is based upon existing WLP infrastrcuture: The core component of this planar integration technology is the embedding of ultra-thin chips into a multi layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Many publications over the last several years have indicated that companies are either already manufacturing 3D chips or have plans to do so in the near future [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Ultimately, the success of any manufacturable 3D integration solution rides on several factors: 1) the choice of TSV technology, which in turn is determined by its compatibility with the rest of the fabrication process, including the bonding stage and method, and the requirements that are placed upon it from a systems perspective; 2) the robustness and thermo-mechanical reliability of the fully integrated structure; and 3) cost/yield considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications over the last several years have indicated that companies are either already manufacturing 3D chips or have plans to do so in the near future [65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Ultimately, the success of any manufacturable 3D integration solution rides on several factors: 1) the choice of TSV technology, which in turn is determined by its compatibility with the rest of the fabrication process, including the bonding stage and method, and the requirements that are placed upon it from a systems perspective; 2) the robustness and thermo-mechanical reliability of the fully integrated structure; and 3) cost/yield considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling shows therefore that 3Di can deliver benefits that are not possible in the 2D regime. Recent publications (3)(4)(5)(6)(7)(8) are an indication that semiconductor manufacturers agree, and have already started 3D chip production or have plans to do so in the near future. However, 3D fabrication involves critical choices in bonding level and method, and TSV process and integration.…”
Section: Introductionmentioning
confidence: 99%